Correction of myocardial electric instability by antioxidant agents - A. E. Radzevich; V. I. Inchina; V. V. Stoljarova; A. Yu. Konjakhin (Российский кардиологический журнал)
In experimental models of pathologic humoral homeostasis (acute renal and hepatic failure, metabolic abnormalities in diabetes mellitus, polyorganic insufficiency in so called tourniquet shock, acute cerebrovascular pathology, etc), significant changes in lipid peroxidation (LPO) process have been observed. These changes cause or worsen myocardial electric instability. Clinical evaluation of emoxipin influence on some LPO parameters, QT interval dispersion (QTd), heart rate variability (ИВУ), late ventricular potentials (LVP) was performed in patients with coronary heart disease, diabetes mellitus, and acute cerebrovascular pathology. Principal possibility of myocardial electric instability prevention has been demonstrated, as well as its correction with antioxidant medications (emoxipin, mexidol, dimephosphon, preductal), in experimental and clinical settings of cardiac and extracardiac pathology.